Geolocation and Federalism on the Internet: Cutting Internet Gambling’s Gordian Knot - King, Kevin F. (Science and Technology Law Review, 2009)
Conventional wisdom dictates that the Internet is a medium in which federalism is destined to fail. By virtue of its decentralized design, the Internet naturally resists regulation by a diverse set of government actors. Indeed, courts have reasoned that federalism on the Internet is either technologically impossible or constitutionally prohibited. The emergence of geolocation technologies, which make it possible to quickly, cheaply, and accurately identify an Internet user’s location, challenges this dominant understanding and opens the door to new approaches that could radically alter the way electronic commerce is governed. To illustrate this point, this Article explores the ways that such technologies could be used to make Internet gambling regulation more responsive to longstanding federalism principles. As demonstrated below, geolocation technologies have the potential to make Internet gambling law both more effective and more efficient by enabling each state to enforce its own substantive regulations.